IMPLEMENTATION OF INTEGRATIVE CURRICULUM MANAGEMENT IN FORMING MUSLIM CHARACTER - Yusuf, Muhammad Yusuf; Fitriono, Ahmad Natsir (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2026)
Curriculum management is crucial in a cooperative, comprehensive, systemic, and systematic curriculum management system to achieve educational goals. One curriculum design is an integrated curriculum, a form of curriculum that eliminates the boundaries of disciplines or subjects and presents the curriculum as a unit or as a whole. This research aims to analyzing the implementation of integrative curriculum management in shaping Muslim character. This research uses a qualitative case study type of research, namely the specification of a case in an incident, whether it includes individuals, cultural groups or a portrait of education in Islamic boarding schools for students. Data collection methods include interviews, observation, and documentation. Data analysis uses interactive analysis. Data validity is verified using credibility, transferability, dependability, and confirmability techniques. The research results found that The implementation of integrative curriculum management in shaping Muslim character refers to the formulation of philosophy which is then internalized in three institutions, dirosah (teaching and learning activities in class), santrian (focus on the creativity, initiative, sensitivity, courage and skills of students) and care (delivery of tausiyah, guidance and direction to students about religious values ​​and social issues. The results of this study strengthen the theory of James A. Beane, there are four dimensions of integrative curriculum, namely a) Integration of experiences. b) Social integration. c) The integration of knowledge, and d) Integration as a curriculum design. The formal conceptual finding regarding integrative curriculum management in shaping Muslim character is transdisciplinary-based integrative curriculum management with an organic integration approach.